A multiplex PCR assay with a common primer for the detection of eleven foodborne pathogens. Issue 3 (30th January 2020) - Tao, Jing; Liu, Wanwan; Ding, Wei; Han, Rong; Shen, Qiang; Xia, Yu; Zhang, Yahan; Sun, Wanping
Abstract : Abstract: Salmonella enterica, Listeria monocytogenes, Shigella flexneri, Escherichia coli O157:H7, Vibrio parahaemolyticus, Staphylococcus aureus, Vibrio cholerae, Clostridium botulinum type A, Bacillus cereus, Clostridium perfringens Alpha toxin, and Yersinia enterocolitica are 11 common foodborne pathogens. Traditional bacterial culture methods for detecting pathogens are time‐consuming and labor‐intensive. Multiplex PCR technology, which can detect multiple targets in a single tube, has been increasingly applied to microbial detection due to its high specificity, sensitivity, and fast response. This paper is to establish a multiplex PCR technology mediated by a common primer for the detection of these 11 common foodborne pathogens in order to achieve the goal of nondirectional screening for these 11 common foodborne pathogens. The specificity of the established CP‐MPCR detection system was first verified by 100 clinical isolates. The sensitivity of the CP‐MPCR detection system was then detected by using cultured bacteria preparations and has been confirmed with a high sensitivity of 10 3 to 10 4 CFU/mL, among them, the sensitivity of the CP‐MPCR for Vibrio cholerae and S. flexneri can even achieve 10 2 CFU/mL. Sixty anal swab samples collected from Suzhou CDC and 16 enrichment cultured solutions of food samples collected from the Suzhou Food Inspection and Testing Center were tested using the CP‐MPCR system. A total of 32 positive results were detected. Practical Application: Food poisoning incidents occur frequently around the world, mainly because of the contamination of food by pathogenic bacteria and serious harm to human health. The method provided in this study can detect 11 foodborne pathogens in food, which can effectively prevent the spread of pathogenic microorganisms. At the same time, for the food poisoning incident that has already occurred, this method can be used for diagnosis to find out the cause.